Pengaruh Harga, Kualitas Produk, dan Promosi Terhadap Keputusan Pembelian di Barley Store Kota Kediri (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of price, product quality, and promotion on consumer purchasing decisions at Barley Store in Kediri City. A quantitative approach was employed using a survey method with questionnaires distributed to 100 respondents who had previously made purchases at Barley Store. The data were analyzed using multiple linear regression. The results show that both partially and simultaneously, the variables of price, product quality, and promotion have a positive and significant effect on purchasing decisions. Among these variables, product quality is the most dominant factor influencing consumer decisions. These findings are expected to serve as a reference for Barley Store's management in developing more effective marketing strategies to enhance customer satisfaction and loyalty